CONSUMERS’ COMMENTS ON ONLINESHOP: DISRUPTION OR JUST CANDID COMMENTS? - Erna Mariana Susilowardhani; Bida Sari (Jurnal InterAct, 2017)
Online shop is an Internet-based business, which is increasing in Indonesia, such as Lazada, Zalora, Tokopedia, Elevenia, Bukalapak, and so on. They attempt to provide maximum service, especially related with security transactions and interesting promotion to capture consumers as much as possible. In an online shop business, usually C to C business, where online shop serves as an intermediary party between merchants with consumers. This can be the weakness because quality of products and services depend on retailers, not the online shop itself, but the responsibility is imposed to the retailers. In this case, numerous comments are given by the consumers who made purchases. Not only positive comments, but also negative ones. The comments typically are on the quality and condition of item, condition of packaging, delivery time, and so on. In this study, researchers looked at the experiences from the consumers of online shops, who tend to respond to comments of other consumers who bought the goods. This research used the concept of e-commerce, and consumer behavior. To deepen understand the experience of consumers, researchers conducted in-depth interviews as the primary data. The informants are consumers who usually purchase through online shops. Authenticity and triangulation of method are used as data validity technique. The results stated that informants pay attention with the comments from previous buyers. They also noticed whether the goods are a favorite (many buyers) or not, including the number of followers (if sold via Instagram), and star sign. If the online shop and sellers’ partners ignore such comments, it will be a disruption for themselves. These findings provide input to online shops to realize the importance of comments from consumers and increase better services, including coaching to the retail merchant partners.